Kummerite, Mn2+Fe3+Al(PO4)2(OH)2·8H2O, a new laueite-group mineral from the Hagendorf Süd pegmatite, Bavaria, with ordering of Al and Fe3+. (2nd January 2018) - Grey, I. E.; Keck, E.; Mumme, W. G.; Pring, A.; Macrae, C. M.; Glenn, A. M.; Davidson, C. J.; Shanks, F. L.; Mills, S. J.
Abstract: Kummerite, ideally Mn 2+ Fe 3+ A1(PO4 )2 (OH)2 .8H2 O, is a new secondary phosphate mineral belonging to the laueite group, from the Hagendorf-Süd pegmatite, Hagendorf, Oberpfalz, Bavaria, Germany. Kummerite occurs as sprays or rounded aggregates of very thin, typically deformed, amber yellow laths. Cleavage is good parallel to ﹛010﹜. The mineral is associated closely with green Zn- and Al-bearing beraunite needles. Other associated minerals are jahnsite-(CaMnMn) and Al-bearing frondelite. The calculated density of kummerite is 2.34 g cm 3 . It is optically biaxial (-), α= 1.565(5), β = 1.600(5) and y = 1.630(5), with weak dispersion. Pleochroism is weak, with amber yellow tones. Electron microprobe analyses (average of 13 grains) with H2 O and FeO/Fe2 O3 calculated on structural grounds and normalized to 100%, gave Fe2 O3 17.2, FeO 4.8, MnO 5.4, MgO 2.2, ZnO 0.5, Al2 O3 9.8, P2 O5 27.6, H2 O 32.5, total 100 wt.%. The empirical formula, based on 3 metal apfu is (Mn 2+ 0.37 Mg0.27 Zn0.03 Fe 2+ 0.33 )Σ1.00 (Fe 3+ 1.06 Al0. 94 )Σ2.00 PO4 )1.91 (OH)2.27 (H2 O)7.73 . Kummerite is triclinic, P1̄, with the unit-cell parameters of a = 5.316(1) Å, b =10.620(3) Å, c = 7.118(1) Å, α = 107.33(3)°, β= 111.22(3)°, γ = 72.22(2)° and V= 348.4(2) Å 3 . The strongest lines in the powder X-ray diffraction pattern are [dobs in Å(I) (hkl)] 9.885 (100) (010); 6.476 (20) (001); 4.942 (30) (020); 3.988 (9) (̄110); 3.116 (18) (1̄20); 2.873 (11) (1̄21). Kummerite is isostructural with laueite, but differs in having Al and Fe 3+ ordered into alternate octahedral sites in the 7.1 Å trans -connected octahedral chains.